Geomagnetic Navigation of Autonomous Underwater Vehicle Based on Multi-objective Evolutionary Algorithm - Li, Hong; Liu, Mingyong; Zhang, Feihu (Frontiers in Neurorobotics, 2017)
This paper presents a multi-objective evolutionary algorithm for Autonomous Underwater Vehicles (AUVs) based on geomagnetic navigation. The disturbance from geomagnetic anomalies often converges to the local optimal, which eventually leads to failure of navigation. To tackle such problem, the principal idea is to introduce a navigation model based on behavior constraints, thereby effectively determining the abnormal area by monitoring the changes of the geomagnetic. In presence of the vehicle trapping into the abnormal area, the behavior constraints are triggered to jump out the abnormal area. In conclusion, the proposed method provides a new idea for underwater vehicles navigation in condition of disturbance from geomagnetic anomalies. The simulation result demonstrates its reliability and feasibility in complex environments.